Ecosystem Observation, Simulation and Assessment (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on ecosystem observation, simulation and assessment. Ecosystems provide supply, regulation, culture and support services for human beings in addition to overall support human survival and sustainable development. However, driven by multiple factors such as climate change, population growth, urbanization, and exploitation of mineral resources, global problems such as ecosystem degradation and biodiversity loss have affected the sustainable development of human beings. Because of this, it has become a hot spot in ecology research to develop basic theories, model methods and technical means for ecosystem observation, simulation and evaluation for the quantitative analysis of the structure, process and function of ecosystems as well as the improvement of the scientific understanding of the changing characteristics and evolution laws of natural ecosystems.